Grey matter atrophy in cognitively impaired Parkinson's disease. Issue 2 (2nd September 2011) - Melzer, Tracy R; Watts, Richard; MacAskill, Michael R; Pitcher, Toni L; Livingston, Leslie; Keenan, Ross J; Dalrymple-Alford, John C; Anderson, Tim J
Abstract : Objective: Mild cognitive impairment and dementia are common non-motor features of Parkinson's disease (PD). The aim of this study was to characterise grey matter changes associated with clearly defined stages of cognitive impairment in PD using structural MRI. Methods: 96 PD subjects were classified using detailed cognitive testing as PD with normal cognition (PD-N, n=57), PD with mild cognitive impairment (PD-MCI, n=23) or PD with dementia (PD-D, n=16); 34 controls matched for mean age and sex ratio also participated. Grey matter volume differences were evaluated using voxel based morphometry of grey matter segments derived from T1 weighted 3 T MRI, and multiple linear regression assessed the relationship between cognitive and motor impairments and grey matter concentration. Results: Compared with controls, no grey matter differences were found in PD-N. PD-MCI showed limited grey matter atrophy in the temporal, parietal and frontal cortex as well as the bilateral caudal hippocampus, amygdala and right putamen. PD-D subjects exhibited far more extensive atrophy in regions involved in PD-MCI but also had reduced grey matter volume in other large areas of the temporal lobe (including the parahippocampi), the intracalcarine and lingual gyri, posterior cingulate gyrus, frontal regions and bilateral caudate. Grey matter loss in PD correlated with global cognitive score but not motor impairment in most of these regions. Interpretation: Marked grey matter atrophy occurs in PD with dementia but far less extensive changes are evident in PD-MCI. Some grey matter atrophy precedes the development of dementia but may be accelerated once frank dementia begins.